The Optimal Design of Crand-Type In volute Planetary Gear Drive - 李爱军; 沈慧芬; 刘殿辉 (Jixie chuandong)
The transmitting ratioes of the crank-type involute planetary gear drive are distributed optimally with aim of drive size minimization and the geometrical parameters of the internal gear pair are determined optimally while maximize its efficiency of engagement in the paper.